Several seam weld finite element idealizations challenged in fatigue within a French industrial collaborative workgroup. (2018) - Bennebach, M.; Klein, P.; Kirchner, E.
Abstract: In industry with fatigue strengthening concern, there are as many ways to make an FE seam weld idealization as factories involved in these types of simulations. Tens of ways to model a seam weld are available as soon as it is necessary to get out of direct connection assumption and if it is needed to take into account local weld stiffness and secondary bending effect of the fillet weld. Then it becomes mandatory to be able to discriminate such idealization processes while evaluating associated life prediction accuracy and industrial idealization efficiency (automation). This concern leads the idea to create a French industrial workgroup including CETIM and about 20 industrial companies, members of the "Mobile Machinery Program Committee". The main goal of this collaborative project being to challenge well documented and most promising seam weld idealization models (with associated methods) to converge at the end towards the most capacitive ones (with better results on given fatigue metrics). As a first part of the multi-partner project work, a complete and precise technical review was achieved, giving a state of the art of the idealization models and methods available. Then the workgroup started extensive comparisons between well documented fatigue tests on seam welded components and associated FEA for some retained models and methods (Fayard, Lohr, IIW Hot Spot Stress, Notch Stress). Several components were considered, with more than 100 fatigue test results. This paper presents most of the obtained results, the Round Robin being still on-going. Preliminary results comparisons demonstrate general applicability of classical methods introduced in the standards or recommendations, these being also in most cases conservative. Results of this work aim to help choosing the right methodology, depending of the seam weld configuration and the in service loadings. It is also intended to try building partnerships with FE software editors to include most efficient methodologies in an automated way, making less tedious the seam weld modelling task on huge chassis frames. Small and medium factories should then reach an efficiency gain and improved accuracy level when building their virtual seam welded frames with new automated scripts integrated in their own FEA solutions.